IJTIHAD YUSUF AL-QARADHAWI: Kebolehan Aborsi Sebagai Solusi Bagi Korban Perkosaan - Ulya, Azma; Firdaus, Firdaus; Hidayat, Rahmat (Al-Maslahah : Jurnal Ilmu Syariah, 2025)
This article analyzes Sheikh Yusuf al-Qaradhawi's ijtihād method regarding the permissibility of abortion for rape victims. The research method used in this study is a literature study using qualitative analysis of the fatwa of Sheikh Yusuf al-Qaradhawi and related documents. In the Qur'an and hadith there is no text that allows abortion, but according to Sheikh Yusuf al-Qaradhawi abortion due to rape is permissible if the udzur is getting stronger then the rukhsah is more clear and if it happens before the age of forty days, then that is closer to rukhsoh (permissibility). The purpose of the rukhsah is to eliminate the harm that occurs to the pregnant woman.